Islamic microfinance for rural farmers: a proposed contractual framework for Amanah Ikhtiar Malaysia - Abidullah Abid; Muhammad Hakimi Mohd Shafiai (Penerbit Universiti Kebangsaan Malaysia, 2017)
Rural poverty is considered as a major challenge for the current economies. In Malaysia, the rural farmers faces problems in the cultivation process due to unavailability of financial support. The support of Department of Agriculture is only limited to first stage of agriculture project, leaving the farmers in problems for the second stage. Hence in this study we have provided a solution to the issues confronted by the famers through the involvement of Amanah Ikhtiar Malaysia. The aim is to involve Amanah Ikhtiar Malaysia to provide support to the rural famers based on the profit and loss sharing scheme unlike the current mode of financing. Before proposing a contractual framework, a qualitative and narrative form of literature review method is used to explore the issues. It is suggested that al-Muzāra‘ah contract is more suitable to provide assistance to the rural famers with the supervision from Department of Agriculture. This study would help not only Amanah Ikhtiar Malaysia but also other microfinance institutions in developing a partnership based contract that would be specifically designed for the poor rural farmers.